(untitled) (Journal of Asian Development Studies, 2024)
Apple is the third largest fruit crop in the country, following citrus and mango, covering a significant area in Baluchistan and playing a crucial role in local income generation and the national economy. This study aimed to assess the awareness levels of respondents regarding management practices. A multi-stage sampling technique was employed, with tehsil Ziarat purposively selected. Four randomly chosen union councils and 12 villages within these councils were included, totaling 120 apple growers interviewed for data collection. The results revealed limited awareness among respondents about mechanical land preparation and the hexagon or triangular planting systems for apple cultivation. Red delicious variety dominated due to market demand, with lesser-known varieties like Mashadi and Amri being less cultivated. Awareness about irrigation methods such as furrow and drip irrigation, and fertigation practices, was also low. Similarly, knowledge about equipment like backpacks and compressed air sprayers was lacking, with manual picking being the most common method. There is a critical need to enhance the knowledge of apple growers through organized extension activities. Additionally, government subsidies on inputs are necessary to equip farmers with the latest agricultural technologies.